Determining The Degree of Genetic Kinship Between Some entered Lentil Genotypes (Lens culinaris Medic) Using ISSR Technique (Damascus University Journal of agriculture sciences, 2025)
In the genetic study that was conducted to determine the degree of genetic kinship between the studied Lentil genotypes (14 entered genotypes + tow variety Idlib3 and Idlib4)  using ISSR technique, a total number of 14 primer were used for this purpose which had proved its effectiveness in giving polymorphisms among the studied genotypes, as they resulted 66 bands. the average number of primer was 4.576 band per primer. The average polymorphisms percentage was 97.14%. The polymorphism information content (PIC) ranged from 0.3432 to 0.4998 with an average of 0.4650, as the used primers proved their ability to distinguish between the studied genotypes. It was found the percent agreement values (PAV) is 0.7176 among the two genotypes X2011s_226_6 and ILL8006 as the lowest value of PAV, which indicates that there is indicates that they have a large variation of genetic relationship between them, while the highest value of PAV was 0.8657 between the two genotypes, X2011s_242_230_3 and X2013_21_2, which indicates that there is a large genetic degree between them.Genetic kinship tree split into two main branches; the one branch included studied genotypes while the second branche included the genotypes X2011s_130_1.
Keywords: Lentils; Genetic Kinship; Polymorphism Information; ISSR